2017
DOI: 10.1038/srep40666
|View full text |Cite
|
Sign up to set email alerts
|

The IL-17A rs2275913 single nucleotide polymorphism is associated with protection to tuberculosis but related to higher disease severity in Argentina

Abstract: Mycobacterium tuberculosis (Mtb) causes nearly 10 millions of new tuberculosis disease cases annually. However, most individuals exposed to Mtb do not develop tuberculosis, suggesting the influence of a human genetic component. Here, we investigated the association of the rs2275913 SNP (G → A) from IL-17A and tuberculosis in Argentina by a case-control study. Furthermore, we evaluated in vitro the functional relevance of this SNP during the immune response of the host against Mtb and analyzed its impact on cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 50 publications
(107 reference statements)
2
36
1
1
Order By: Relevance
“…TB and control population in the present study did not agree with the H-W equilibrium and have ethnic differences. In other studies, there were showed H-W equilibrium in PTB and control population for rs2275913 SNP in Polish and Argentina population [26,27]. Du et al and Shi et al [28,29] showed that the IL-17A rs2275913 was found to be in line with H-W equilibrium in controls in a Chinese population.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…TB and control population in the present study did not agree with the H-W equilibrium and have ethnic differences. In other studies, there were showed H-W equilibrium in PTB and control population for rs2275913 SNP in Polish and Argentina population [26,27]. Du et al and Shi et al [28,29] showed that the IL-17A rs2275913 was found to be in line with H-W equilibrium in controls in a Chinese population.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, in southern Brazilian population, the A allele and GA genotype were associated with increased risk for TB development [32]. In Argentina population, Rolandelli et al [27] found positively associated between AA genotypes from the IL-17 rs2275913 SNP and protection to active TB and finally, in North Indians, it was found that the frequency of genotype GA 86 (52.1%) for SNP rs2275913 is higher than the frequency of both genotype GG 17 (10.3%) and AA 43 (41.1%) [19]. According to the results of this study, the frequency of A and G alleles of IL-17 rs2275913 gene polymorphisms in Iraqi normal population were 50% for both alleles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been demonstrated that the substitution of the G by an A allele in the IL17A rs2275913 gene promoter was significantly associated with autoimmune diseases and cancer [33][34][35][36] . However, controversial results have been reported regarding the levels of IL-17A in serum, where the A allele was associated with a higher 20,36,37 , lower 38,39 or no significant 40 levels of transcription and synthesis of the protein. In this work, we could hypothesized that the individuals who carry the A allele in the IL17A rs2275913 would be more susceptibility to the T. cruzi infection, probably due to a variation in the gene Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the rs2275917 SNP may reflect the autoimmune‐related function of IL‐17A. With regard to the function of IL‐17A in preventing infection, the AA genotype of the rs2275913 SNP was shown to be associated with protection against tuberculosis but also higher disease severity, hepatitis B virus (HBV) resistance, and Bacillus Calmette–Guérin (BCG) osteitis after vaccination . These findings indicate that the AA genotype of the rs2275913 SNP has advantages for preventing infections, whereas this genotype overall leads to more severe inflammation.…”
Section: Introductionmentioning
confidence: 99%